Pharmacokinetics profile of pentagamavunon-0 after potassium pentagamavunonat-0 oral administration in rats - Arief Rahman Hakim; Agung Endro Nugroho; Lukman Hakim (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
Potassium PGV-0 was a salt form of PGV-0 which has been developed to be a new medicine. The salt form was relatively water soluble and therefore was is expected to have better bioavailability and efficacy than the parent compound.The research aims were to investigate the pharmacokinetics profiles of PGV-0 after the administration of its potassium salt per orally in male rats Wistar The treadment was done by using a completely randomized design to explore the profiles of PGV-0 in blood, its distribution into primary organs : liver, kidneys, lungs and small intestine, and also its elimination into urine and feces in the animals. Potassium PGV-0 was given single doses per orally at 40 and 80 mg/kg BW. The analytical assay for PGV-0 was conducted by an HPLC method with a UV-Vis detector.The results shown that according to per oral administration of K-PGV-0 to the rats, there was no PGV-0 found in the blood monitored up to 360 minutes. The compound was not found in the liver nor kidneys, and only traces (<5% of dose) were found in the lungs or small intestine. Traces amounts of PGV-0 were also found in urine or feces. The extremely rapid disappearance of the compound from the blood may not be due to its rapid distribution into the organs but more likely due to its fast biotransformation in the blood or in the liver. This assumption is also supported by the facts that PGV-0 found in the urine or feces was negligible (< 5% of administered dose).Key words : potassium pentagamavunon-0, pentagamavunon-0, pharmacokinetics